How bad is the rain? Applying the extreme rain multiplier globally and for climate monitoring activities - David A. Lavers; Gabriele Villarini; Hannah L. Cloke; Adrian Simmons; Nigel Roberts; Anna Lombardi; Samantha N. Burgess; Florian Pappenberger (Meteorological Applications)
Abstract A typical question posed following an extreme precipitation event is: How does this compare to past events? This question is being asked more frequently and is of importance to climate monitoring services, such as the Copernicus Climate Change Service (C3S). Currently, the statistics extensively used for this purpose are not generally understandable to the wider public, or they are not tailored towards presenting extremes. To mitigate this situation, this article uses a modified version of the Extreme Rain Multiplier (ERM), which was developed for tropical cyclones, and applies it to precipitation events globally. For daily precipitation considered herein, the ERM is calculated by dividing the daily precipitation accumulation during an event by the mean historical annual maxima of daily precipitation (RX1day), which is computed over 1991–2020. Using the European Centre for Medium‐Range Weather Forecasts ERA5 reanalysis, the calculation of the ERM is illustrated for six extreme events around the world; these included convective systems, atmospheric rivers and tropical cyclones. A maximum ERM of 4 was found during Storm Daniel, in Greece, and in Tropical Cyclone Jasper in Australia, implying that four times the mean RX1day precipitation occurred. The ERM will be useful in C3S reporting activities because it can objectively identify extreme precipitation events. Furthermore, after extracting the number of precipitation events per year at each grid point that had an ERM exceeding 1, a trend analysis was undertaken to ascertain if the frequency of extreme events had changed with time. Results showed that the most widespread increasing trends in the ERM were in the tropics, but these trends are thought to be questionable in ERA5. There were few clear trends in other regions. In conclusion, the ERM can communicate the level of extreme precipitation in a clear manner and can be used in climate monitoring activities.